Kajian Longsoran pada Area Lereng untuk Pengembangan Perumahan - Ahmad Junaidi (Jurnal Tekno Global, 2019)
AbstractIn late November 2017, the Cempaka tropical cyclone which occurred in the southern coastal waters of the island of Java, resulted in high rainfall causing landslides in landfill and damage to the retaining wall of a residential area in Kasihan Sub-District, Bantul Regency.Stability analysis of retaining walls using Geo5 software with bolster stability review, shear stability, soil bearing capacity and decreases that occur with soil parameters based on CPT testing and earthquake load with acceleration values with a PGAM value of 0.5g.The results of the analysis of the existing retaining wall without seismic load obtained a rolling stability value with a safety factor 1.38. Slip field stability with safety factor 1.11. The capacity of soil bearing capacity with safety factor 0.9. Soil reduction of 43.9 mm and slope stability with safety factor 1.35. Based on the results of the analysis, the retaining wall is declared unsafe by referring to the safety factor of the Geo5 ASD software. The plan to strengthen cantiliver wall type retaining wall was modeled with Geo5 software to produce dimensions with height of 9 m and footting dimensions 6.55 m with safety factor 2.63 for rolling stability, 3.14 for slip field stability, 3.80 for soil bearing capacity and soil degradation of 75.50 mm. Based on the results of the analysis, the retaining wall is declared safe with reference to the safe number of the Geo5 ASD software.Keywords : retaining wall, static load, safety factorAbstrakPada akhir November 2017, siklon tropis Cempaka yang terjadi di perairan pesisir selatan pulau Jawa, mengakibatkan curah hujan yang tinggi menyebabkan kelongsoran pada tanah timbunan serta kerusakan pada dinding penahan tanah suatu kawasan perumahan yang berada di Kecamatan Kasihan, Kabupaten Bantul. Analisis stabilitas dinding penahan tanah menggunakan software Geo5 dengan tinjauan stabilitas guling, stabilitas geser, daya dukung tanah serta penurunan yang terjadi dengan parameter tanah berdasarkan pada pengujian CPT serta beban gempa dengan nilai percepatan dengan nilai PGAM 0.5g. Hasil analisis dinding penahan tanah eksisting tanpa beban gempa didapatkan nilai stabilitas penggulingan dengan angka aman 1,38. Stabilitas bidang gelincir dengan angka aman 1,11. Kapasitas daya dukung tanah dengan angka aman 0,9. Penurunan tanah sebesar 43,9 mm dan stabilitas lereng dengan angka aman 1,35. Berdasarkan hasil analisis tersebut, dinding penahan tanah dinyatakan tidak aman dengan mengacu pada angka aman ASD software Geo5. Rencana perkuatan dinding penahan tanah tipe cantiliver wall di modelkan dengan software Geo5 menghasilkan dimensi dengan tinggi badan 9 m dan dimensi footting 6,55 m dengan nilai angka aman 2,63 untuk stabilitas penggulingan, 3,14 untuk stabilitas bidang gelincir, 3,80 untuk kapasitas dukung tanah dan penurunan tanah sebesar 75,50 mm. Berdasarkan hasil analisis tersebut, dinding penahan tanah dinyatakan aman dengan mengacu pada angka aman ASD software Geo5.Kata kunci : dinding penahan tanah, beban statis, faktor aman